Pendidikan Islam di Era Jepang: Antara Pembatasan dan Peluang - Nurul Auliyah HS; Qahar M; Idrus L (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
This article examines the dynamics of Islamic education in Indonesia during the Japanese occupation (1942–1945), focusing on two policy roles that both restricted and created opportunities for institutions such as pesantren, Muhammadiyah, and Aisyiyah. Using a critical literature review method, this study identifies two main aspects: institutional restrictions that affected educational activities and opportunities that emerged in the recruitment of teaching staff, curriculum development, and the role of organizations. The results indicate that despite being under strict supervision, Islamic institutions were able to adapt and innovate, thereby contributing to the formation of Islamic educational identity in the post-independence era. These developments remain crucial for understanding current challenges in Islamic education.